(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effects of extravasated fluid on the airway pressure of the patients in different surgical positions.Material and Methods: This prospective observational study included 50 arthroscopic shoulder surgery patients (18-65 years) placed in lateral decubitus (Group L) and beach chair (Group B) positions under general anesthesia. Peak airway pressure (Ppeak) and internal PEEP (iPEEP) measurements were recorded after intubation. The neck, chest, and shoulder circumferences were measured before induction and after operation.Results: The increases in Ppeak and iPEEP values were not statistically significant between the groups (p> 0.05). The total amount of irrigation fluid was significantly higher in Group L (p=0.042), not significantly correlated with Ppeak but positively correlated with the surgery time (r=0.51099; p=0.001 0.05). The neck circumference measurements were statistically significant between the groups. No respiratory complications were observed during the follow-up period.Conclusion: The lateral decubitus and beach chair positions do not cause a clinically significant compromise on the airway pressure in arthroscopic shoulder surgery but a longer operation duration will cause a higher amount of irrigation fluid to be used, leading to an increased circumference of the neck in the postoperative period.Keywords: Shoulder arthroscopy; airway pressure; lateral decubitus position; beach chair position